PERAN BRAND AMBASSADOR ATLET BADMINTON DALAM MEMBANGUN BRAND AWARENESS PADA PRODUK OLAHRAGA YONEX - Aiyu Masfufah; Meistra Budiasa (LP2M STP Mataram, 2023)
Brand ambassadors are currently widely used by companies to carry out marketing activities. Athletes or popular people have many followers who believe in them as models or role models. Their ability to persuade makes them able to promote products. The research method uses a descriptive qualitative approach. In this research, researchers used interview, observation and documentation methods. The key informants in this research are Yonex salespeople and badminton athletes sponsored by the Yonex sports brand, while the informants are Yonex customers who have purchased Yonex products. The research results revealed: 1. The marketing communication strategy through SWOT analysis in Yonex brand sports products was carried out in several steps, including identifying targets, designing messages, and determining communication channels using badminton athletes. 2. Yonex's strength is that the quality and quality of the products it sells is guaranteed and that it has brand ambassadors for outstanding athletes. Yonex also has several opportunities, such as the growth in popularity of sports such as badminton and tennis which have experienced significant growth in popularity in various countries, Yonex has the opportunity to collaborate with famous athletes and sports teams.